Uji Formulasi Pupuk Organik Cair Berbahan Aktif Bacillus sp. Pada Pembibitan Utama Kelapa Sawit (Elaeis guineensis Jacq) - Hutabarat, Richart; Puspita, Fifi; Khoiri, M. Amrul (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Palm oil (Elaeis guineensis Jacq) is a crop plantation were a high economic value because it is a vegetable oil plant. In Indonesia, oil palm is important to increasing the country's income and able to improve people's fare well, especially in Riau Province. The study aimed to examine the effect of formulations liquid organic fertilizer contain active Bacillus sp. and get the best formulations on the growth of oil palm seedlings (Elaeis guineensis Jacq). The research was conducted in Quarantine Laboratory, Pekanbaru and in the technical implementation unit of agriculture faculty of Riau University, in April until to October 2013. The methods of research is experimentally with using randomized block design (RBD) with 5 treatments and 4 replications. The data were analyzed statistically with using analysis of variance and followed by Duncan’s New Multiple Range Test at level α = 5%. The parameters measured were increase of seedling height, increase of the number of midrib, increase of circle stem, seedling root volume, root crown ratio and dry weight of plants. The results of the research showing that all treatment of formulations Bacillus sp. were tested has non significant effect on all parameters of observation. Formulations of Bacillus sp. with coconut water is the best formulation in increasing of palm oil seedling height and the tendency towards in increase of number of the midrib and plant dry weight. Keywords : Bacillus sp, organic fertilizer liquid and palm oil